_turnip_
turnip sleepy as a turnip - (turnip is pronounced turnup) Refers to, usually, a sleepy child and has reference to fact a turnip "sleeps" in the ground when it is growing or after it has grown & immediately prior to harvest. I'm unsure of which is correct. Yes Used I Used I Not used poison [see 'turmits'] NEWFOUNDLAND FOLKLORE SURVEY.